MicroRNA binding site polymorphisms as biomarkers in cancer management and research - Cipollini M; Landi S; Gemignani F (Dove Medical Press, 2014)
Monica Cipollini, Stefano Landi*, Federica Gemignani* Department of Biology, University of Pisa, Pisa, Italy *These authors contributed equally to this work Abstract: MicroRNAs (miRNAs) are important regulators of eukaryotic gene expression. They have been implicated in a broad range of biological processes, and miRNA-related genetic alterations probably underlie several human diseases. Single nucleotide polymorphisms of transcripts may modulate the posttranscriptional regulation of gene expression by miRNAs and explain interindividual variability in cancer risk and in chemotherapy response. On the basis of recent association studies published in the literature, the present review mainly summarizes the potential role of miRNAs as molecular biomarkers for disease susceptibility, diagnosis, prognosis, and drug-response prediction in tumors. Many clues suggest a role for polymorphisms within the 3' untranslated regions of KRAS rs61764370, SET8 rs16917496, and MDM4 rs4245739 as SNPs in miRNA binding sites highly promising in the biology of human cancer. However, more studies are needed to better characterize the composite spectrum of genetic determinants for future use of markers in risk prediction and clinical management of diseases, heading toward personalized medicine. Keywords: miRSNP, 3'-UTR target binding site, cancer risk, biomarkers